Self-Antigen Presentation by Dendritic Cells in Autoimmunity - Hopp, Ann-Katrin; Rupp, Anne; Lukacs-Kornek, Veronika (Frontiers in Immunology, 2014)
The operation of both central and peripheral tolerance ensures the prevention of autoimmune diseases. The maintenance of peripheral tolerance requires self-antigen presentation by professional antigen presenting cells (APCs). Dendritic cells (DCs) are considered as major APCs involved in this process. The current review discusses the role of DCs in autoimmune diseases, the various factors involved in the induction and maintenance of tolerogenic DC phenotype and pinpoints their therapeutic capacity as well as potential novel targets for future clinical studies.